PERAN GAPOKTAN KARYA BERSAMA DALAM IMPLEMENTASI PROGRAM PEREMAJAAN SAWIT RAKYAT (PSR) DI BANDAR DURIAN, AEK NATAS, LABUHAN BATU UTARA - Maharani, Azizah; Laksmono, Bambang Shergi (Jurnal Pembangunan Manusia, 2021)
This research discusses the role of the oil palm joined farmer groups in the implementation of People’s Oil Palm Rejuvenation program (PSR). The PSR program is a program designed by the government to assist oil palm farmers in increasing the productivity of oil palm farmers and supporting Sustainable Rural Development which impacts on improving the welfare of oil palm farmers. In the PSR program, the role of oil palm farmer groups is very important, as they are the grant beneficiaries and managers, so that the success or failure of the program also depends on the farmer groups. In this study, the role of farmer groups will be analyzed in terms of decision making, Human Resources (HR) mobilization and management, communication and coordination, and mediation of problems. This study used a qualitative method with a purposive sampling method. The result of this research is in terms of decision making to follow PSR program, the head of the farmer group must convince the oil palm farmers if the program can run well. During the implementation of the PSR program, communication and coordination between Gapoktan and the agriculture agency went well, where extension workers played an important role in liaising communication between farmer groups and the agriculture agency, but there was a slight miscommunication with the partnership namely regarding the making of the RAB (Draft Budget) and implementation in the field. In HR mobilization and management, the farmers' lack of knowledge has resulted in non-optimal administrative management. The PSR program is also not separated from problems so that there is a need for problem mediation, namely at stage three where farmer groups will no longer use partnerships because they are already experienced, so they can manage the grant independently. This research suggests that institutional strengthening is needed so that farmers can be independent farmers who can run their own programs and there is a need for clear main duties and functions from each stakeholders of the PSR program.